ANALYSIS OF ATHLETES' TECHNIQUES AND STRATEGIES IN SEPAK TAKRAW MATCHES IN DOUBLE EVENT NUMBERS (CASE STUDY OF PRE PON SEPAK TAKRAW REGION III 2023) - Victor, Victoria Eka Prasetyo; Yudha Kusuma , Donny Wira; Sri Hanani, Endang (Journal of Physical Education and Sports, 2024)
Analysis of athletes' skills, techniques and strategies in sepak takraw matches is important to create training programs to improve athletes' ability to compete. The purpose of this study is to analyze the service, smash, and block skills  in the men's athlete competition in Pre pon 2023. The match video was recorded in 6 sets of the Pre Pon region III 2023 men's sepak takraw final match using a video camera placed behind the field. The data analysis technique in this study uses an independent sample t test with the help of the SPSS statistical application for windows version 26.0. The results showed that the ability of service and smash on the winning team with the loser there was no significant difference. Both teams have good skills in terms of service and smash in sepak takraw matches. The results of the hypothesis test for block  ability show a difference between the winning team and the losing team. The winning team has  a lower fail block compared to the losing team. The results of the analysis found that the strategy that can be done by the sepak takraw athlete team is to increase the ability to block so as to reduce the failure rate in blocking. This aspect is what makes one of the teams lose the match.